Effects of Acute Prolonged Sitting and Interrupting Prolonged Sitting on Heart Rate Variability and Heart Rate in Adults: A Meta-Analysis - Bates, Lauren C.; Alansare, Abdullah; Gibbs, Bethany Barone; Hanson, Erik D.; Stoner, Lee (Frontiers in Physiology, 2021)
Prolonged sitting increases cardiovascular disease (CVD) risk, however the physiological mechanisms contributing to CVD from acute sitting exposure are not well-understood. Therefore, this study investigated the heart rate (HR) and variability (HRV) responses to prolonged sitting and after interrupting prolonged sitting (e.g., walking). Electronic databases were searched (inception-August 2020) for studies which exposed adults to prolonged (≥1 h) sitting with and/or without interruptions. Twenty-one articles (27 trials, n = 537) met inclusion criteria. Prolonged sitting non-significantly increased HR (weighted mean difference (WMD) = 0 bpm, 95% CI: −2, 3) and HRV (standardized mean difference (SMD) = 0.12, 95% CI: −0.08, 0.33) compared to pre-sitting baseline. Interrupting prolonged sitting yielded a non-significant small increase in HR (WMD = 4 bpm, 95% CI: 0, 7) compared to pre-sitting baseline. Sub-group analyses investigating interrupting prolonged sitting revealed small-to-moderate increases in HR in healthy populations (WMD = 6 bpm, 95% CI: 1, 10) and following walking interruptions (WMD = 7 bpm, 95% CI: 3, 11). In conclusion, prolonged sitting does not significantly affect HR or HRV. However, interrupting prolonged sitting yielded a small non-significant increase in HR, potentially indicative of increased metabolic demand. Further research is needed to investigate poor CVD outcomes via autonomic disruption from prolonged sitting.